Electrical impedance spectroscopy and structural characterization of liquid-phase sintered ZnO-V2O5-Nb2O5 varistor ceramics doped with MnO - Pandey S.; Kumar D.; Parkash O. (My University, 2025)
The influence of the MnO content on the microstructure and the electrical response of liquid-phase sintered ZnO-V2O5 varistor ceramics wereanalysed using A.C. impedance spectroscopy on samples prepared via the conventional solid state route.The impedance spectra were analysed with the help of one model equivalent circuit at high frequencies and another at low frequencies, involving both resistor and non-Debye constant phase elements (CPEs). The results indicate a significant contribution of grain boundary resistance to the total resistance and non-ohmic characteristic of the studied materials. The Arrhenius plots show two slopes with a turnover at 150 °C/200 °C for both the higher- and lower-frequency time constants. These behaviours can be related to the decrease of the minor charge carrier density. These activation energies were associated with the adsorption and reaction of O2 (as well as V) species at the grain boundary interface. Consequently, better varistor performance is achieved for 96.9 mol% ZnO+0.5 mol% V2O5+0.10 mol% Nb2O5+2.5 mol% MnCO3 with nonlinear coefficient α=21.6, breakdown field E1mA=191.47 V/mm, leakage current density JL=36.46 μA/cm2 and activation energies of 0.639 eV and 0.644 eV. X-ray diffraction shows that in addition to the major ZnO phases, Zn3(VO4)2 and ZnV2O4, were detected as minor secondary phases. SEM analysis of the morphology shows that the grain growth increases with increases in the MnO doping level. © 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.